Pengaruh Pemberian Reward Transaksional Orangtua terhadap Prestasi Siswa Di SMK N 1 Saptosari - Anna Novita (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
The purpose of the study is to examine the effect of transactional rewards to the students ’achievement. This study is very important because it explains that hard work and responsibility is stronger than rewards in supporting children to gain achievement. The approach of the study was quantitative method with explanatory research, because variables that were studied would explain the object of the study through the collected data. The subject of the study was the students of XI TKJ o f SMK N 1 Saptosari. The sample consisting 32 students were examined by questionnaires as the data collection technique. The result of the study showed that transactional rewards has 15, 63% effect to the students ‘achievement in SMK N 1 Saptosari.